2019
DOI: 10.5194/acp-19-2259-2019
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and mixing state of north African mineral dust by online single-particle mass spectrometry

Abstract: Abstract. The mineralogy and mixing state of dust particles originating from the African continent influences climate and marine ecosystems in the North Atlantic due to its effect on radiation, cloud properties and biogeochemical cycling. However, these processes are difficult to constrain because of large temporal and spatial variability, and the lack of in situ measurements of dust properties at all stages of the dust cycle. This lack of measurements is in part due to the remoteness of potential source areas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 118 publications
5
18
0
Order By: Relevance
“…These instruments were used to provide real time information on size and chemical composition for individual particles and bulk samples, respectively. The LAAPTOF is a commercially available single particle mass spectrometer and has been well described in recent publications (Ahern et al, 2016;Gemayel et al, 2016;Gemayel et al, 2017;Marsden et al, 2018;Marsden et al, 2016;Marsden et al, 2019;Ramisetty et al, 2018;Reitz et al, 2016;Shen et al, 2018;Shen et al, 2019). In brief, aerosol particles with a size range of 70 nm to 2.5 m vacuum aerodynamic diameter (dva) are sampled with a flowrate of ~80 cm 3 min -1 , focused and accelerated via an aerodynamic lens (ADL).…”
Section: Measurement Site and Instrumentationmentioning
confidence: 99%
“…These instruments were used to provide real time information on size and chemical composition for individual particles and bulk samples, respectively. The LAAPTOF is a commercially available single particle mass spectrometer and has been well described in recent publications (Ahern et al, 2016;Gemayel et al, 2016;Gemayel et al, 2017;Marsden et al, 2018;Marsden et al, 2016;Marsden et al, 2019;Ramisetty et al, 2018;Reitz et al, 2016;Shen et al, 2018;Shen et al, 2019). In brief, aerosol particles with a size range of 70 nm to 2.5 m vacuum aerodynamic diameter (dva) are sampled with a flowrate of ~80 cm 3 min -1 , focused and accelerated via an aerodynamic lens (ADL).…”
Section: Measurement Site and Instrumentationmentioning
confidence: 99%
“…The transmission efficiency of the inlet as a function of size has also been accounted when considering size distributions for particles up to 10 µm. Inlet penetration as a function of size has also been considered based on the Andersen 321A PM 10 inlet (McFarland, 1984).…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Analysis of the LAAP-ToF data acquired during the ICE-D intensive campaign has been presented by Marsden et al (2019), in which the mineralogy and mixing state of North African dust transported to the Cape Verde Islands is described in detail with reference to dust samples collected on the ground from potential source areas in North Africa. Using a combination of cluster analysis and sub-compositional analysis, that work showed that differences in mineralogical composition of ground https://doi.org/10.5194/acp-2020-157 Preprint.…”
Section: Data Analysis Methodsmentioning
confidence: 99%